2013
DOI: 10.1523/jneurosci.4702-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Inhibitory Molecule NG2 Improves Synaptic Transmission, Retrograde Transport, and Locomotor Function after Spinal Cord Injury in Adult Rats

Abstract: NG2 belongs to the family of chondroitin sulfate proteoglycans that are upregulated after spinal cord injury (SCI) and are major inhibitory factors restricting the growth of fibers after SCI. Neutralization of NG2's inhibitory effect on axon growth by anti-NG2 monoclonal antibodies (NG2-Ab) has been reported. In addition, recent studies show that exogenous NG2 induces a block of axonal conduction. In this study, we demonstrate that acute intraspinal injections of NG2-Ab prevented an acute block of conduction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 88 publications
2
57
0
Order By: Relevance
“…The choice of this dual treatment was based on the knowledge that accumulation of chondroitin sulfate proteoglycans (CSPGs;Dou and Levine 1994;Galtrey and Fawcett 2007;Silver and Miller 2004;Snow et al 1990) and insufficient neurotrophin support (Arvanian 2013;Fortun et al 2009;Grill et al 1997;Mendell et al 2001;Schnell et al 1994) are major reported obstacles known to restrict better recovery after SCI. Degradation of CSPGs with the enzyme ChABC was shown to promote sprouting of fibers following cervical crush (Barritt et al 2006;Bradbury et al 2002), hemisection (Houle et al 2006Iseda et al 2008), transection (Fouad et al 2005, and contusion (Caggiano et al 2005;Tom et al 2009, but see Iseda et al 2008 injuries.…”
Section: Stony Brook Stony Brook New Yorkmentioning
confidence: 99%
See 4 more Smart Citations
“…The choice of this dual treatment was based on the knowledge that accumulation of chondroitin sulfate proteoglycans (CSPGs;Dou and Levine 1994;Galtrey and Fawcett 2007;Silver and Miller 2004;Snow et al 1990) and insufficient neurotrophin support (Arvanian 2013;Fortun et al 2009;Grill et al 1997;Mendell et al 2001;Schnell et al 1994) are major reported obstacles known to restrict better recovery after SCI. Degradation of CSPGs with the enzyme ChABC was shown to promote sprouting of fibers following cervical crush (Barritt et al 2006;Bradbury et al 2002), hemisection (Houle et al 2006Iseda et al 2008), transection (Fouad et al 2005, and contusion (Caggiano et al 2005;Tom et al 2009, but see Iseda et al 2008 injuries.…”
Section: Stony Brook Stony Brook New Yorkmentioning
confidence: 99%
“…Transverse sections (40 m) of T 6 -T 8 were used for reconstructions of acute lesions and L 1 -L 5 for 5-HT immunostaining. Cresyl violet staining was used to determine spinal cord segmental levels and reconstructions of injury and acute lesions as previously described (Arvanian et al 2006;Petrosyan et al 2013). For immunofluorescence staining, sections were washed with 0.3% Triton X-100 in PBS, blocked with 5% normal goat serum in 0.3% Triton X-100 in PBS for 2 h at room temperature, and then incubated in appropriate primary antibodies: rabbit anti-5-HT [1:1,000, ImmunoStar for serotonin (5-HT) immunoreactivity] or mouse antibody to chondroitinase-generated C-4-S (2B6, 1:200, Mdbioproducts) overnight at 4°C.…”
Section: Immunohistochemistry and Quantitative Analysismentioning
confidence: 99%
See 3 more Smart Citations